2001
DOI: 10.1108/eum0000000005923
|View full text |Cite
|
Sign up to set email alerts
|

Green purchasing practices of US firms

Abstract: Over the last two decades, growing concerns about eroding ecosystem quality have led to a renewed interest in environmentalism. Such concerns have prompted purchasing professionals to reassess their current purchasing strategy. To help purchasing professionals configure an environmentally conscious (green) purchasing strategy, the empirical findings from a survey of US firms with greater environmental risks are reported. Based on the empirical findings, aims to identify variables that either promote or inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
386
2
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 577 publications
(422 citation statements)
references
References 11 publications
10
386
2
8
Order By: Relevance
“…Finally, the organizational size can play a role as well. In the for-profit world, among buying firms, those with larger purchasing volumes are more likely to be involved in green purchasing than smaller ones (Min & Galle, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, the organizational size can play a role as well. In the for-profit world, among buying firms, those with larger purchasing volumes are more likely to be involved in green purchasing than smaller ones (Min & Galle, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…The proper knowledge of these barriers is required to apply GSCM practices successfully. Authors 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 Min and Galle (2001) found in their research that lack of knowledge in society means, customers are still not conscious of green products and their benefits to the society. Walker et al (2008) found that there are a number of complications such as fear of poor environment performance disclosure, lack of confidentiality & information.…”
Section: Literature Review For Barriers Of Gscmmentioning
confidence: 99%
“…Lack of understanding to incorporate green buying, inappropriate organizational structure and cost reduction at the cost of environment are known as internal barriers of GSCM. According to Min and Galle, (2001) in their research in US firms found that cost concern is the most severe hindrance for employing environmental aspects into account in purchasing process.…”
Section: Internal Barriersmentioning
confidence: 99%
“…This is considered as the mother of all drivers and leaves no option for a firm but to comply with it or exit the market. (Hall, 2001;Min and Galle, 2001;Zhu and Sarkis, 2006;Walker et al, 2008, Hsu et al, 2013, have all identified in their research, government regulation and legislation as the main enabler of GSCM. Government commitment to sustainability can promote a sustainable culture and can drive clients and contractors serving the government to Title comply with sustainability aspects such as ISO 14001 certifications, green building guidelines etc.…”
Section: Review On Gscm Enablersmentioning
confidence: 99%
“…Chan and Makino (2007) have identified mimetic isomorphism; a strategy to imitate other firms in the sector especially competitors. The involvement of top management (Min and Galle, 2001). Vachon and Klassen (2006) identified leadership capabilities of individuals with commitment to environmental issues will determine the adoption of GSCM.…”
Section: Review On Gscm Enablersmentioning
confidence: 99%